2021
DOI: 10.1002/aoc.6192
|View full text |Cite
|
Sign up to set email alerts
|

Tungstic acid (H4WO5) immobilized on magnetic‐based zirconium amino acid metal–organic framework: An efficient heterogeneous Brønsted acid catalyst for l‐(4‐phenyl)‐2,4‐dihydropyrano[2,3c]pyrazole derivatives preparation

Abstract: A new magnetic nanocatalyst based on the immobilization of tungstic acid onto new design robust, cost‐effective, green, and scalable zirconium‐L‐aspartate amino acid metal–organic framework (MOF)‐grafted L‐(+)‐tartaric acid stabilized magnetite nanoparticles (Fe3O4/tart‐NPs) was synthesized by two successive solvo (hydro)‐thermal methods. This catalyst was characterized by Fourier‐transform infrared (FT‐IR), energy‐dispersive X‐ray spectroscopy (EDS), X‐ray diffraction (XRD), field‐emission scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…4 and 5 ). The acceptable surface area and small size of the Fe 3 O 4 @SiO 2 @-MIP-202 nanocomposite may be also due to the preparation method [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 and 5 ). The acceptable surface area and small size of the Fe 3 O 4 @SiO 2 @-MIP-202 nanocomposite may be also due to the preparation method [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows a comparison of the recently reported synthesis methods of 1,4dihydropyrano[2,3-c]pyrazole-5-carbonitrile derivatives such as triazine-based functionalized HY zeolite [40], SBA-15/hydrotalcite/heteropoly acid (phosphotungstic acid) [50], tungstic acid immobilized on zirconium-L-aspartate amino acid metal-organic frameworkgrafted L-(+)-tartaric acid-stabilized magnetic Fe 3 O 4 nanoparticles [51], yttrium iron garnet [52], triphenylphosphine [53], sugarcane bagasse ash-based silica-supported boric acid [54], and 1,3-dimethyl-2-oxo-1,3-bis(4-sulfobutyl) imidazolidine-1,3-diium hydrogen sulfate[DMDBSI]2HSO4 [55] a catalyst.…”
Section: Results Of Four-component Synthesis Of Multi-ring Compound C...mentioning
confidence: 99%
“…Sajjadi et al (2023), for instance, reported on the synthesis of dihydropyrano[2,3c]pyrazoles via Knoevenagel-Michael multiple reactions by using green catalyst Fe 3 O 4 @gC 3 N 4 for the reaction of aldehydes, phenylhydrazine, ethyl acetoacetate and malononitrile under 1 h reflux to achieve 97 % yield of product (Route 1). [51] This reaction has also been reported by using numerous catalysts such as 1,8-diazabicyclo[5.4.0]-undec-7-en-8-ium acetate ([DBU][Ac], [59] HMS/PrÀ Rh-Zr, [60] H 3 PO 4 /Al 2 O 3 , P 2 O 5 /SiO 2 , starch sulfuric acid, cellulose sulfuric acid, [61] thiourea dioxide (TUD), [62] PVCÀ EDAÀ CeIII, [63] citrus limon (lemon juice), [64] agave leaf ash extract, [65] piperidine, [66] sodium lactate, [67] NiWO 4 , [68] PBCMOamine, [69] CaO nanoparticles, [70] Fe 3 O 4 @chitosan-tannic acid bionanocomposite, [71] FSiPSS nano-catalyst, [72] nano ZrO 2 , [73] lactic acid : urea : NH 4 Cl, [74] H 4 [SiW 12 O 40 ], [75] NiFe 2 O 4 @SiO 2 À H 3 PW 12 O 40 (NFSÀ PWA), [76] Fe 3 O 4 @SiO 2 @CoSB, [77] PAN@melamine/Fe 3 O 4 nanocomposite, [78] isonicotinic acid, [79] nano-[Fe-PSMP]Cl 2 , [80] Fe 3 O 4 /MIP-202-H 4 WO 5 , [81] Zn(L-proline) 2 , [82] baker's yeast, [83] solar radiation, [84] Cu-DABP@Fe 3 O 4 /MCM-41, [85] Fe 3 O 4 @NFC@Co(II), [86] PdO/Al-SBA-15, [87] (MnCoFe 2 O 4 @Niacin-SO 3 H) + Cl À , [88] Zn-CA-MOFs [89] and Na 2 CaP 2 O 7 . [90] In 2022, Nguyen and coworkers reported different routes to the synthesis of pyrano[2,3-c]pyrazole derivatives, which involved a four-component reaction of benzyl alcohols, phenylhydrazine, ethyl acetoacetate and malononitrile with the aid of sulfonated amorphous carbon and eosin Y as c...…”
Section: Synthesis Of Pyranopyrazole and Its Derivativesmentioning
confidence: 99%